An Intelligent Water Management Framework for Irrigating Urban Gardens in Technologically Advanced Cities (International Journal of Scientific Research in Science and Technology, 2024)
The Innovative Water Management Protocol for Urban Garden Irrigation within Smart Cities introduces a novel strategy for sustainable urban agriculture. This approach harnesses cuttingedge technologies to optimize water usage in irrigation, integrating intelligent sensors, data analysis, and automated processes. By utilizing uptodate information on soil moisture, weather patterns, and plant requirements, the protocol ensures precise and effective water distribution, minimizing waste. Moreover, it integrates IoTenabled devices for remote monitoring and management, enabling urban gardeners to oversee irrigation systems effortlessly via mobile applications. This initiative not only conserves water resources but also fosters environmental sustainability and resilience in response to climate change. Additionally, it enhances food security by promoting efficient urban farming techniques. The Innovative Water Management Protocol illustrates the harmonious relationship between technology and agriculture, contributing to the development of smarter and more environmentally friendly urban environments.